Bacteremia after Bacillus clausii administration for the treatment of acute diarrhea: A case report - Juan Pablo García; Julián Andrés Hoyos; John Alexander Alzate; Edilberto Cristancho (Biomédica, 2021)
Bacillus clausii is a gram-positive rod used as a probiotic to treat diarrhea and the side effects of antibiotics such as pseudomembranous colitis. We report a case of B. clausii bacteremia in a non-immunocompromised patient with active peptic ulcer disease and acute diarrhea. The probiotic was administered during the patient´s hospitalization due to diarrhea of infectious origin. B. clausii was identified in the bloodstream of the patient through Matrix-Assisted Laser Desorption Ionization-Time of Flight (MALDI-TOF) days after her discharge. Given the wide use of probiotics, we alert clinicians to consider this microorganism as a causative agent when signs of systemic infection, metabolic compromise, and hemodynamic instability establish after its administration and no pathogens have been identified that could explain the clinical course.